Perceived Racial/Ethnic Discrimination Predicts Worse Global Cognition in a Diverse Sample. (30th August 2019) - Morris, E; Guzman, V; Tell, E; Summers, A C; Clark, U S; Byrd, D A; Rivera Mindt, M; Arce Rentería, M
Abstract: Objective: While perceived racial/ethnic discrimination (PD) and HIV can be independently detrimental to cognitive function, it is unclear whether persons living with HIV (PLWH) who experience PD may be at risk for greater cognitive dysfunction than HIV- persons. In a diverse sample, we hypothesized that PD would be related to worse cognition and that this effect would be moderated by HIV status. Participants and Method: This cross-sectional study included 53 participants (57% PLWH; 77% African American and 23% Latinx; 45% male; M Age = 54.5 ± 6.1 years; M Education = 12.4 ± 2.2 years) who completed the Perceived Ethnic Discrimination Questionnaire (PEDQ) and a neurocognitive (NC) battery. Variables included education (years); HIV status; PEDQ Total Score and global NC T-score (averaged, demographically-corrected T-scores for all tests). A general linear model examined main and interaction effects of HIV status and PD on global cognitive function. Covariates included depression and urine toxicology status for cocaine and marijuana. Results: Greater PD was associated with higher education and greater depression. The model showed that greater PD (β = -.48, p < .05) and lower education (β = -19.0, p < .01) were related to worse global cognitive function. This relationship was moderated by education (β = .59, p < .01), such that the relationship between PD and global cognitive function was stronger in those with higher education. There was no main effect of HIV or HIV*PD interaction on global cognitive function. Conclusions: This study demonstrated that greater PD is related to worse global cognitive function and this relationship is stronger in those with more education. While no causal factors can be attributed, racial/ethnic minorities with higher education may be granted greater access to areas with greater structural racism and/or microagressions (i.e., predominantly white workplaces). Future studies should evaluate the role of socioeconomic and workplace diversity when considering discrimination.